Modelo de decisão multicritério para seleção de fornecedores de equipamentos laboratoriais para pesquisa agropecuária - RODRIGUEZ, Jenny Milena Moreno (2017)
One of the strategies to guarantee the economic development in a country is represented by the agricultural improvements reached in terms of technological innovation for development of new products or techniques of analysis. Since the success of a research is determined by the performance found in the laboratory tests, is essential that such innovations are reflected also in the laboratory activities. Although there are several studies focused on agricultural research, few actually refer to the administrative procedures that guarantee the availability of physical resources and that consequently influence the driving of researches. In order to enrich and increase the productivity, firms need methodologies that lead generate a competitive advantage within the market, reflected in economic benefits. The supplier selection is one of the most important tasks from the economic perspective for many organizations and is therefore a classic multiple criteria decision problem because it includes conflicting goals and whose decision may influence the competitiveness of the company. In this context, this work proposes building a multicriteria model for supplier selection of laboratory equipment, which the preferences of the decision makers are analyzed under different cases of purchases. Since the difficulties encountered during the preferences evaluation process, the Interactive and Flexible Tradeoff (FITradeoff) elicitation method was used to overcome these limitations. Compared to traditional procedure, FITradeoff method showed the advantage of not requiring exact values of indifference from the decision maker, and of needing fewer questions to reach the solution. The model was applied at a Colombian agricultural research company, to choose the alternative with the best overall performance. The results showed that the final solution achieved was not the cheaper in terms of sale price, which shows that a single criteria approach based only on cost factors, that often occurs in practice, may not be enough to guarantee the fulfillment of the purchasing process, and to achieve the organizational objectives.